Ceramics based on reactional connected silicon nitride used for foundry crucibles - S. Usherenko; V. Ovtchinikov; V. Shmuradko; N. Kirshina (Литьë и металлургия, 2000)
Is elaborated а composite material based on reactional connected silicon nitride for refractory crucibles.